Development and characterization of high internal phase pickering emulsions stabilized by heat-induced electrostatic complexes particles: Growth nucleation mechanism and interface architecture. (15th February 2023) - Wang, Lechuan; Xiao, Bowen; Guo, Qiannan; Guo, Panpan; Zhang, Huajiang; Chi, Yujie; Xia, Ning; Jiang, Longwei; Cui, Qian
Highlights: Heat-induced electrostatic complex particles (HIECP) were prepared by different ways. Pectin (PE) reinforced the colloidal stability and rigidity structure of HIECP. The novel HIPPEs had different interface architecture and stabilization mechanisms. The curcumin-loaded HIPPEs exhibited extraordinary photochemical stability. Abstract: In this work, the heat-induced ovalbumin (OVA)-pectin (PE) electrostatic complex particles (HIECP) prepared by different heating sequences (type I particles (I): Heat-treated ovalbumin/pectin complexes at pH 4; type II particles (II): Complexes between pre-heated ovalbumin and pectin at pH 4) and biopolymer ratios were used as stabilizers to form high internal phase Pickering emulsions (HIPPEs). The results showed that I had a more compact structure, higher net surface charge, and smaller particle size than II, due to the different growth nucleation mechanism. II-stabilized HIPPEs exhibited a smaller oil droplet size, stronger gel structure, and better stability than I-stabilized HIPPEs, owing to their suitable wettability, rigid "core–shell" structure, and robust and dense interface architecture. Moreover, the stability and gel-like structure of HIECP-stabilized HIPPEs improved with increasing PE content due to steric barrier and thickening effects. Our findings provide a new perspective for understanding heat-induced biopolymer particles as effective Pickering stabilizers.